Investigation of properties of nitride and silicon oxide films grown by plasma-chemical deposition on a silicon substrate - Rubtsevich I. I.; Solovyov Ya. A.; Vysotskiy V. B.; Dudkin A. I.; Kovalchuk N. S. (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature, 2011)
The research has been carried out on dependence of mechanical stress on the modes of deposition of silicon nitride and oxide films obtained by plasma excited chemical vapour deposition of the layers from the gas phase (PECVD). The connection has been determined between the key parameters of the deposition, such as operating pressure in the chamber, working gas consumption, deposition rate and the level of internal mechanical stresses.